Does Alkaline Colonic pH Predispose to Clostridium difficile Infection?. Issue 2 (February 2016) - Gupta, Purba; Yakubov, Stanley; Tin, Kevin; Zea, Diego; Garankina, Olga; Ghitan, Monica; Chapnick, Edward K.; Homel, Peter; Lin, Yu Shia; Koegel, Michael M.
Abstract : Objectives: Clostridium difficile caused nearly 500, 000 infections and was associated with approximately 29, 000 deaths in 2011, according to data from the Centers for Disease Control and Prevention. C. difficile is a bacterium that causes diarrhea and, often, severe illness in healthcare facilities, as well as the community. Our objective was to determine whether alkaline colonic pH predisposes to colonization and infection with C. difficile . Methods: A total of 228 patients with diarrhea and/or abdominal pain, leukocytosis, and fever were included. Stool pH was measured, and C. difficile antigen and toxin in stool were detected. Results: Of 228 patients, 30 (13.2%) tested positive for C. difficile (antigen+/toxin+) and 171 (75%) were C. difficile negative (antigen−/toxin−). Of 171 patients who tested negative, 93 (54.4%) had stool pH >7.0 and 78 (45.6%) had pH ⩽7.0. Among the 30 patients who tested positive, 26 (86.7%) had stool pH >7.0 ( P = 0.002). Among the 27 colonized patients (antigen+/toxin−), 12 (44.4%) had stool pH >7.0 ( P = 0.34). For all patients with stool pH ⩽7.0, 96% tested negative for C. difficile infection ( P = 0.002). Conclusions: A strong association between C. difficile infection and alkaline stool pH was found. Abstract : The authors' research project was conducted at Maimonides Medical Center in conjunction with the Division of Infectious Diseases for the study of Clostridium difficile infections. The hypothesis on which they based their research was does the environment surrounding certain bacteria affect their growth? The authors studied the growth patterns of Clostridium difficile and noted that its growth is pH dependent. The authors then analyzed stool specimens to confirm their hypothesis.